Ellis-van Creveld syndrome: A rare clinical entity - Kamal, Reet (Medknow Publications & Media Pvt Ltd, 2013)
Ellis-van Creveld (EVC) syndrome is a genetic disorder with autosomal recessive transmission, which may clinically present as small stature, short limbs, fine sparse hair, hypoplastic fingernails, multiple musculofibrous frenula, conical teeth, hypoplasia of the enamel, hypodontia, and malocclusion. Heart defects, especially abnormalities of atrial septation, have been found in about 60% of cases. The mutation in EVC and EVC2 gene is responsible for this syndrome. The presence of multiple orodental findings makes this syndrome important for dentists. The aim of this article is to present a rare case of EVC syndrome in a 10-year-old girl along with the review of literature.